Digital Peace: Social Media’s Role in Shaping Global Harmony and Conflict - Dr. Farhana Kousar; Muhammad Ali Panhyar; Dr. Muhammad Ramzan (`, 2025)
The ascendancy of social media as a global public square has created a profound paradox, positioning digital platforms as central yet ambivalent forces in shaping contemporary global affairs. This article investigates the dual role of social media in simultaneously fostering global harmony and exacerbating destructive conflict, a dynamic central to the emerging concept of "Digital Peace." Employing a qualitative mixed-methods approach including comparative case studies of the Rohingya crisis and the Türkiye-Syria earthquake response, documentary analysis of policy reports, and thematic analysis of scholarly literature this research delineates the specific mechanisms driving these opposing outcomes. The findings reveal that algorithmic architectures, designed for engagement maximization, systematically amplify misinformation, engineer polarization, and facilitate the mobilization of hate speech and extremist actors. Conversely, the study also documents social media’s capacity for effective crisis coordination, cross-cultural empathy-building, and the strategic deployment of peacebuilding counter-narratives. The discussion, framed through theoretical lenses of Social Identity Theory and the Social Shaping of Technology, argues that this duality is not inherent to the technology but is a direct consequence of its current economic model and a significant global governance gap. The article concludes by synthesizing these insights into a multi-stakeholder framework for achieving Digital Peace, proposing four critical pillars: enforceable platform accountability and algorithmic transparency; smart, human rights-based regulatory frameworks; comprehensive digital and media literacy education; and the strategic mobilization of civil society for digital peacebuilding. This study contends that the future of global harmony depends on our collective ability to consciously reshape the digital ecosystem to prioritize civic health and human dignity over unbridled engagement. Keywords: Digital Peace, Social Media Conflict, Algorithmic Amplification, Platform Governance, Digital Literacy, Peacebuilding, Misinformation, Global Harmony